Energy storage for power system planning and operation - Hu, Zechun, 1979- (John Wiley & Sons Singapore Pte. Ltd, 2020)
"An introduction to the rapidly evolving field of energy storage systems, this book provides a valuable framework for understanding the existing and latest technologies for integrating energy storage applications with power systems. It begins with a review of the state of the art and supplements that with system models and simulations. Readers will gain an understanding of the various techniques that can be employed for energy storage that is compatible with renewable energy generation. The practical aspects of system optimization, planning and siting are also covered in detail"--